2018
DOI: 10.3390/buildings8050063
|View full text |Cite
|
Sign up to set email alerts
|

Phase Change Materials for Building Applications: A Thorough Review and New Perspectives

Abstract: Abstract:The purpose of this paper is to provide a comprehensive report on the state of the art on the technologies used in the modeling of energy storage systems by latent heat in buildings, and draw lines on perspectives on the technology evolution in this sector. In the first part, the emphasis is put mainly on the two main lines of research: experimental and numerical. In the second part, the main trends of research in this sector have been followed. An anatomical operation of more than 100 documents (publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…Therefore, O-PCMs work exceptionally well on buildings of low thermal mass [16], where temperatures change abruptly, giving place to high energy consumption associated with thermally conditioning the building. The results of several investigations have proven that a proper design is necessary to take advantage of the capabilities of PCMs like the reduction of energy consumption, and the improvement of thermal comfort in buildings [17]. In a passive strategy, the integration of PCMs into building materials allows releasing of heat during the colder hours, beginning the solidification process.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, O-PCMs work exceptionally well on buildings of low thermal mass [16], where temperatures change abruptly, giving place to high energy consumption associated with thermally conditioning the building. The results of several investigations have proven that a proper design is necessary to take advantage of the capabilities of PCMs like the reduction of energy consumption, and the improvement of thermal comfort in buildings [17]. In a passive strategy, the integration of PCMs into building materials allows releasing of heat during the colder hours, beginning the solidification process.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, PCMs have been an attractive field of study for scholars aiming at optimizing buildings' energy efficiency. In fact, by incorporating such materials into buildings lightweight envelopes, thermal inertial of the building envelope could significantly improve while providing a natural regulation of internal temperature [12]. A major characteristic of phase change materials is their capability of being used in different building components.…”
Section: Fig 1 Iot Based Monitoring Devicementioning
confidence: 99%
“…According to chemical composition phase change materials can be classified into three categories namely organic compounds, inorganic compounds and inorganic eutectics or eutectic mixtures(Baetens, R., Jelle, B. P., & Gustavsen, 2018). The organic compounds can be further categorized into paraffin's and non-paraffin.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the use of PCM is increasing rapidly, PCM changes its phase by absorbing heat energy from the sun, if it is solid then convert in liquid and if in liquid than convert in solid, At the time of day, PCM kept inside the solar energy in the form of thermal energy, then by changing its phase at night it loose the heat energy in building, which can also keep the building warm while using natural energy at night. (Baetens, R., Jelle, B. P., & Gustavsen, 2018). Several studies have demonstrated that the use of PCMs in well-insulated buildings can reduce heating and cooling energy in residential buildings by as much as 25% and obtain similar reductions in the peak power required for air conditioning.PCM reduce the load of heater in winter season and also reduce the AC (Air conditioner) load in summer.…”
Section: Introductionmentioning
confidence: 99%